Elbow prosthesis revision with custom-made ulnar stem - Asparago, Giovanni; Toro, Giuseppe; Mastrodonato, Federica; Astone, Alberto; Vitali, Giacomo; Calabrò, Giampiero (Lo Scalpello - Journal, 2024)
Introduction. Total elbow arthroplasty (TEA) is a relatively infrequent orthopedic procedure compared to other types of arthroplasty operations, such as knee and hip replacements. To date, the indications have expanded to include non-synthesizable distal humerus joint fractures, osteoarthritis, and post-traumatic arthritis. Case presentation. A 75-year-old woman presented to the emergency room following an accidental fall at home. Radiographic control revealed a distal diaphyseal fracture of the humerus on the left with complete paralysis of the radial nerve and mobilization of the ulnar stem of the TEA on the right. It was decided for an initial reduction and synthesis of the left distal humerus fracture with a plate and screws and subsequent partial revision surgery of the TEA. In the following two weeks of follow-up, significant skin distress generated by the apex of the ulnar stem was observed. We proceeded with synthesis and partial reconstruction of the ulna with cadaver bone and plate and screws before the definitive operation. After approximately 3 months, we proceeded with the definitive operation to remove the fixation devices and revision of the ulnar component of the TEA. At 12 months of follow-up, the patient had excellent results with a slight deficit in extension and flexion, without painful symptoms. Conclusions. TEA revision is an increasingly frequent intervention. This is due to the gradual increase in primary implants, but also due to the expansion of surgical indications. The main causes of revision are component loosening and post-trauma periprosthetic fractures. In the present case, the revision surgery of the ulnar component of a TEA with a custom- made stem was associated with satisfactory clinical and radiographic results throughout follow-up. There are few articles in the literature dealing with this topic. To date, revision of TEA is still a challenge due to the complexity of the operation and related complications.